Genetic manipulation of ureteric bud tip progenitors in the mammalian kidney through an Adamts18 enhancer driven tet-on inducible system - Rutledge, Elisabeth A.; Lindström, Nils O.; Michos, Odysse; McMahon, Andrew P. (Developmental biology, 2020)
The ureteric epithelial progenitor (UEP) population within the embryonic kidney generates the arborized epithelial network of the kidney’s collecting system and plays a critical role in the expansion and induction of the surrounding nephron progenitor pool. Adamts18 shows UEP- restricted expression in the kidney and progenitor tip-restricted expression in several other organs undergoing branching epithelial growth. Adamts18 is encoded by 23 exons. Genetic removal of genomic sequence spanning exons 1 to 3 led to a specific loss of Adamts18 expression in UEPs, suggesting this region may encode a UEP-specific enhancer. Intron 2 (3 ​kb) was shown to have enhancer activity driving expression of the doxycycline inducible tet-on transcriptional regulator (rtTA) in an Adamts18en-rtTA transgenic mouse strain. Crossing Adamts18en-rtTA mice to a doxycycline dependent GFP reporter mouse enabled the live imaging of embryonic kidney explants. This facilitated the analysis of ureteric epithelial branching events at the cellular level. Ablation of UEPs at the initiation of ureteric bud outgrowth through the doxycycline-mediated induction of Diphtheria Toxin A (DTA) generated a range of phenotypes from complete kidneys agenesis, to duplex kidneys with double ureters. The latter outcome points to the potential of regulative processes to restore UEPs. In contrast, overexpression of YAP prior to ureteric bud outgrowth led to a complete failure of kidney development. Elevating YAP levels at later stages retarded branching growth. A similar phenotype was observed with the overexpression of MYC within the branch-tip localized UEP population. These experiments showcase the utility of the Adamts18en-rtTA transgenic model to the investigation of cellular and molecular events specific to branch tip progenitors within the mammalian kidney complementing existing CRE-dependent genetic tools. Further, the illustrative examples point to areas where new insight may be gained into the regulation of UEP programs. •Adamts18 expression demarcates epithelial branch tip progenitors for several organs.•Genetic analysis identified an Adamts18 enhancer specific to ureteric progenitors.•A tet-on inducible transgenic mouse line enabled genetic modulation in these cells.•The novel line facilitates dynamic high-resolution imaging of ureteric branching.•Tip ablation and YAP/MYC overexpression studies give insights into tip cell actions.